Da tradição oral ao texto escrito: trabalho com a escrita em sala de aula - GONÇALVES, Roseli Ferreira da Costa (Universidade Federal do Pará, 2023)
In this study, we discuss an experience of writing appropriation in Portuguese Language classes by students from a 5th-grade class at Rotary Municipal School, located in the city of Belém, in the Condor neighborhood. The research was based on multiple writing and rewriting activities centered around the study of legends. Our overall objective was to describe the marks of an individual who engages with and works with language through the appropriation of “legends” via writing. To achieve this, we proposed the following specific objectives: a) establish a comprehensive diagnostic assessment of the students' writing skills at the initial stages; b) identify indicators that reveal the subject's effort to appropriate linguistic knowledge at different levels within school writing instruction activities; c) identify signs of "creative" appropriation of legends by students through their written productions; d) discuss the possibilities for developing a language education centered on the subject's engagement with and utilization of language within the context of current teaching and research practices. The theoretical framework was guided by authors adopting the interactionist perspective, including Volóchinov ([1979] 2018) and the Bakhtin Circle, Geraldi (2011, 2013, 2015, and 2019), Franchi (1995), Gancho (2006), and Possenti (2002 and 2009). Our research methodology involved Action Research, as presented in its fundamental principles by Thiollent and Colette (2014) - contract, participation, changes, discourse, and action. Our focus was on a descriptive-qualitative research with a diagnostic nature, in which we conducted observation, investigation, and reflection on the outcomes of our own teaching practice. In the classroom, we conducted multiple activities centered around the axes of writing and textual rewriting, following Geraldi's (2011) concept of writing as work. Through our experience, we demonstrated that the process of student text writing appropriation occurs through interaction, practice, and reflection. The subject's writing consists of voices that resonate in word choices, expressions, and ways of perceiving the world, revealing the establishment of writing processes that allow students to become authors.